Accessibility Of The Exhibition Room For Disability At The Vredeburg Fort Yogyakarta Museum - Citra Dewi Apriliandari; Andreas Sudjud Dartanto; Dian Ajeng Kirana (TUMATA: Journal of Arts and Cultural Management, 2025)
This research aims to identify accessibility facilities in the permanent exhibition space of diorama 1, diorama 2, diorama 3, and diorama 4 of the Yogyakarta Vredeburg Fort Museum for visitors with physical disabilities and visual impairments. The research method used in this research is descriptive qualitative research methods involving visitors with physical disabilities and sensory impairments who have visited the permanent diorama exhibition room, staff at the Fort Vredeburg Yogyakarta Museum, as well as teachers and art activists in the context of people with disabilities in Yogyakarta. The theoretical approach used in this research is the theory of museums, exhibition spaces, accessibility, people with disabilities, as well as human rights and social inclusion. The research results show that the accessibility facilities in the museum exhibition room meet the standards in the form of the availability of automatic doors, corridors, manuvering areas, rams and guide tiles. However, accessibility facilities do not fully accommodate people with physical disabilities who are physically impaired and who are visually impaired due to the lack of adequate rams with handrails, audio descriptions, braille text and tactile objects. This research suggests that museums can improve accessibility facilities that are not yet available to increase comfort and convenience regarding the narrative they want to convey through the collection layout and information labels presented in accordance with inclusive building design standard regulations for visitors with physical disabilities and sensory impairments when visiting the space. permanent display of dioramas at the Fort Vredeburg Museum in Yogyakarta.